Kunanyia stephaniae gen. nov. & sp. nov. (Lepidoptera: Geometridae: Ennominae): an unusual and rare diurnal moth from the mountains of Tasmania - Byrne, Catherine J.; Wei, Nasen (Zootaxa, 2012)
We describe the adult, egg, and all larval stages of a new geometrid moth, Kunanyia stephaniae gen. nov. and sp. nov. Although the genus can be placed in the tribe Nacophorini on key morphological features, it possesses a unique suite of characters that distinguish it from other described nacophorines. Larvae reared from eggs obtained from field-collected females, survived to maturity feeding on the dead leaves of Eucalyptus coccifera and other Eucalyptus spp, an unusual foodplant for Geometridae. To date, adults have only been collected in montane habitats on Mt Wellington near Hobart and Mt Bishop and Clerk, Maria Island, Tasmania.